International Business Cycles: World, Region, and Country-Specific Factors - Kose, M. Ayhan; Otrok, Christopher; Whiteman, Charles H (American Economic Review, 2003)
The paper investigates the common dynamic properties of business-cycle fluctuations across countries, regions, and the world. We employ a Bayesian dynamic latent factor model to estimate common components in macroeconomic aggregates (output, consumption, and investment) in a 60-country sample covering seven regions of the world. The results indicate that a common world factor is an important source of volatility for aggregates in most countries, providing evidence for a world business cycle. We find that region-specific factors play only a minor role in explaining fluctuations in economic activity. We also document similarities and differences across regions, countries, and aggregates.